“ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO, PARA LOS ADJUDICATARIOS DEL MERCADO MUNICIPAL DE LA CIUDAD DE CARIAMANGA, CANTÓN CALVAS, PROVINCIA DE LOJA - Cañar Agurto, Jenny del Carmen (2019)
The present thesis consists of a feasibility study for the implementation of a Savings Bank, in order to facilitate access to financial services to the successful tenderers of the Cariamanga Municipal Market, with easily accessible transactions, which promote the well-being of the community. So a study is shaped in order to determine whether it is feasible to carry it out, in such a way as to satisfy the needs of the successful tenderers. In the elaboration of the work the inductive, analytical, deductive and bibliographic method was used, with the latter a literature review was structured, the same containing a number of topics, which constitute the basis and informative guide for the elaboration of the student. Techniques used as direct observation and the survey which was applied to the 192 successful tenderers of the Cariamanga Municipal Market, in order to search, analyze, and select the appropriate information, by which the objectives of the Cariamanga was achieved present investigative work as part of the following studies: In the market study, reference was made to the collection and analysis of data, information that allows to identify the type of customer and their needs, knowing their economic conditions, income and egress, how they save and the entities they go to in in the case of a credit, allowing us to know what the effective partners would be, that is, those who would actually be part of the Fund as partners, in order to justify the implementation of the savings bank. In the technical study, it was possible to indicate the installed capacity and the capacity used in potential savings and demand for credit of the box, defined its macro and microlocation, project engineering, adequate technology, physical space and human resources Necessary. In the legal administrative study, a model of administrative structure was designed through organizational charts and function manual, for the efficient performance and use of resources, and it also highlights how it will be constituted and the Regulations of the Fund, under the rules and laws in force. Finally, the financial study was carried out, to know the costs, expenses and revenues of the project; the project was evaluated, through the application and analysis of financial indicators such as: Net Current Value obtaining a value of $4.701,89; internal rate of return of 43,58% higher than the TMAR of 7,92%; Profit Ratio Cost of $1.24 which shows that for 5 every dollar invested you will get a profit of $0.24 ctvs. The Investment Recovery Period which will recover in 2 years approximately, 5 months y 20 days and finally the Sensitivity Analysis which allowed to know that the box endured a decrease in revenue of 0,51% and an increase of 0,615% of its costs. On this basis, it can be shown that the realization of the project is feasible technically, financially and administratively, since it has the indicated number of partners, willing to be part of the constitution of the savings bank. Staff would be reduced, with the chairman, credit committee and a cashier being paid, because the limited number of members does not demand much staff